3D printed bioactive glasses porous scaffolds with high strength for the repair of long-bone segmental defects. (1st April 2023) - Liao, Muheng; Zhu, Shuangli; Guo, Anjie; Han, Xiyuan; Li, Qingtao; Chen, Yi; Liu, Yuwei; Chen, Dafu; Chen, Xiaofeng; Mo, Shuixue; Cao, Xiaodong
Abstract: The clinical treatment of long bone segmental defects (LBSD) remains a challenge worldwide due to the deficiency of bone transplantation donors. Developing bone tissue engineering scaffolds similar to cortical in strength and biological activity is a feasible solution. In this work, bioactive glasses with different ratios of copper and magnesium (Cu/MgBGs) were fabricated, and then processed by 3D printing and sintered at 700 °C to obtain porous BGs scaffolds with high strength and no crystallization. The compressive strength of Cu/MgBGs scaffolds with a high porosity (50.99 ± 1.2%) reached 109.27 ± 8.18 MPa, which matched the strength of cortical bone (90–150 MPa). The mineralization experiments confirmed that the scaffolds had good bioactivity before and after sintering. In vitro experiments showed that different ratios of Cu/Mg in BGs had a decisive role in osteogenesis and angiogenesis. Cu0.5/Mg7.5 group had an optimal osteogenic performance while Cu1.0/Mg7.0 group was best for angiogenesis. Also, the antibacterial experiment illustrated that the scaffolds had a good bacterial killing rate of above 95.29 ± 1.02%, which could effectively avoid the infection and broadened the application scenario of the scaffolds. In vivo animal experiments revealed that Cu0.5/Mg7.5 scaffold group had the best bone repair effect on rabbit radius segmental defect with the highest volume and quality of new bone formation. Therefore, Cu0.5/Mg7.5 BGs scaffolds provided an alternative option for the treatment of LBSD. Graphical abstract: Image 1 Highlights: Cu/MgBGs can be sintered without crystallization. Cu/MgBGs scaffolds achieve the balance of porosity-strength-bioactivity. Osteogenesis, angiogenesis and antibacterial properties are promoted by adjusting the ratio of Cu/Mg in BG composition. Cu/MgBGs scaffold can help to repair the long-bone segmental defect (LBSD).